2019
DOI: 10.3389/fpsyt.2019.00727
|View full text |Cite
|
Sign up to set email alerts
|

Attachment and Substance Use Disorders—Theoretical Models, Empirical Evidence, and Implications for Treatment

Abstract: introduction: The article reviews attachment-oriented research in individuals with substance use disorders (SUDs). Based on attachment theory, substance abuse can be understood as "self-medication," as an attempt to compensate for lacking attachment strategies. Attachment theory suggests a developmental pathway from insecure attachment to SUD and, on the other hand, a negative impact of substance abuse on attachment security. Earlier reviews have indicated a general link but have been inconclusive with regard … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
43
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(62 citation statements)
references
References 76 publications
5
43
1
2
Order By: Relevance
“…At the point of referral, the typical situation is one of breakdown in the major attachment relationships across the family. This is consistent with the empirical findings of a bidirectional relationship between attachment insecurity as both an antecedent predictor of substance use disorder, but also that substance use induces further deterioration in the quality and functioning of close relationships (54). In some cases, there is strong intergenerational transmission and one is dealing with the adolescent offspring of parents with a history of substance abuse (64).…”
Section: The Adolescent As Proxy: the Referral And Presenting Problemsupporting
confidence: 89%
See 2 more Smart Citations
“…At the point of referral, the typical situation is one of breakdown in the major attachment relationships across the family. This is consistent with the empirical findings of a bidirectional relationship between attachment insecurity as both an antecedent predictor of substance use disorder, but also that substance use induces further deterioration in the quality and functioning of close relationships (54). In some cases, there is strong intergenerational transmission and one is dealing with the adolescent offspring of parents with a history of substance abuse (64).…”
Section: The Adolescent As Proxy: the Referral And Presenting Problemsupporting
confidence: 89%
“…These include findings of a strong association between preoccupied-enmeshed and substance use in a sample of orphans (57). The other adolescent studies of this type have found associations between avoidant-dismissing and unresolved-disorganized representations in a variety of different substance using groups (54). Adult studies of substance abuse have found associations with Lyons Ruth's hostile-helpless pattern and also with the Main coding of unresolved/disorganized (58).…”
Section: Review Of Attachment Related Predictors Of Addictionmentioning
confidence: 95%
See 1 more Smart Citation
“…The abuse of different types and forms of substances may generate different levels of addiction and harm [2,51], which in turn may trigger distinct social maladjustment and craving behaviors [12,52]. Therefore, future research should discern and clarify the effects of different types and forms of substances on the progress, abstinence and relapse of addicts; this would lead to a better comprehension of the nature and impact of substance abuse.…”
Section: Discussionmentioning
confidence: 99%
“…Der häufige Aufenthalt in kontrollfreier Umgebung, mangelnder Rückhalt in der Familie und leichter Zugang zu Alkohol gelten als weitere Risikofaktoren [25]. An Persönlichkeitsmerkmalen stellt ein spezifisch ausgeprägtes Neugierverhalten ("novelty seeking" oder "sensation seeking") einen prognostischen Faktor für den frühen den Konsum psychotroper Substanzen dar [26], auch unsichere Bindungsmuster sind klar als Risikofaktoren für Suchterkrankungen im allgemeinen und Alkoholabhängigkeit im speziellen erhöhen [27]. Häufig findet sich ausgeprägter juveniler Alkoholkonsum weiters co-morbid bei Jugendlichen mit Aufmerksamkeitsdefizit-Hyperaktivitäts-Syndrom, Angststörungen und depressiven Syndromen sowie bei Jugendlichen, welche in ihrer Geschichte frühe Traumatisierungen aufweisen [28].…”
Section: Persönliche Und Familiäre Faktorenunclassified